SEGMENTASI PASAR PADA PUSAT PERBELANJAAN MENGGUNAKAN FUZZY C-MEANS (STUDI KASUS: RITA PASARAYA CILACAP) - Nurhikmah Megawati; Moch. Abdul Mukid; Rita Rahmawati (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2013)
RITA Pasaraya Cilacap is the first supermarket in Cilacap. Previously, RITA Pasaraya become a shopping center for all people in Cilacap. Now, more and more supermarket is standing. To find this target, RITA Pasaraya needs grouping or market segmentation. Grouping method used fuzzy cluster means (FCM). For an optimal cluster number using the accuracy of the measurement criteria is Xie Beni Index. Research data obtained by questionnaire on RITA Pasaraya Cilacap with 10 psikografik variables. Results of the research, consumer segmentation more accurate if grouped into 2 clusters. The final result is respondents in cluster 1 more attention to low price levels, complete goods, big discounts, satisfactory service, strategic location, roomy parking, comfortable for shopping, adequate public facilities, complete payment facilities, and cleaner room than to respondents in cluster 2. Basically, similar profiles cluster in cluster 1 and cluster 2. Mainly RITA Cilacap Supermarkets are women, with the range age of 16-29 years, with a frequency of shopping 2-4 times per month. Only last education and income are different. In cluster 1, dominated b senior high school with income of 2-5 million every month, and in cluster 2 dominated by bachelor with income <2 million every month.